Effectiveness of acupuncture combined with auricular acupressure in the treatment of postoperative ileus: a study protocol for a randomized controlled trial - Lyu, Ruoyun; Wen, Zonglin; Huang, Rong; Yang, Zhiling; Chen, Yingqun (Frontiers in Surgery, 2024)
Background About one-third of patients experience postoperative ileus (POI) after abdominal surgery, which can cause various complications and has not been treated well in clinical practice. The comprehensive treatment offered by traditional Chinese medicine may be a good choice for promoting intestinal mobility. Therefore, the aim of this study protocol is to observe the effectiveness of acupuncture combined with auricular acupressure in decreasing the incidence and related symptoms of POI. Methods This is a single-center, assessor-blinded, randomized controlled trial. A total of 160 participants are supposed to recruit at Shanghai Tenth People's Hospital and randomly divided into two parallel groups in a 1:1 ratio. The intervention group are planned to receive manual acupuncture combined with auricular acupressure, while the control group are planned to receive regular enhanced recovery after surgery treatment. The primary outcome is the time to first defecation and first flatus after surgery. The secondary outcomes include the length of postoperative hospital stay, intensity of postoperative abdominal pain and distension, severity of postoperative nausea and vomiting, time to tolerate diet, inflammatory index, and incidence of prolonged postoperative ileus. Discussion The results of this research will provide substantial evidence regarding the efficacy of comprehensive traditional Chinese treatment, specifically auricular acupressure and manual acupuncture, in treating and preventing POI. Trial registration ClinicalTrials.gov, Identifier: ChiCTR2300075983, registered on September 21, 2023.